Trade Creation and Trade Diversion Analysis as Impact of Acfta Towards Indonesian Import - Ilham Romadona; Amin Pujiati (Economics Development Analysis Journal, 2018)
This study aim to determined and analyzed the impact of trade creation and diversion of ASEAN China Free Trade Area (ACFTA) on five commodity imports of Indonesian non-oil and gas. This study used a gravity model approach to estimate the flow of trade that occurs and the impact of trade creation and trade diversion. The data used in this study is secondary data, using the method of regression analysis of common effects panel data. The results showed that Indonesia's GDP and exporter countries had a positive and significant impact on Indonesian imports. Distance, population, state boundaries and Regional Trade Agreement Indonesia (RTAI) variables that explain the impact of trade creation and trade diversion significantly influence the import of Indonesian non-oil commodities. The coefficient of determination Adjusted R2 in the range 68%-85% shows the independent variable explains the influence of 68%-85% to the dependent variable, the rest explained other variables outside the model. The impact of ACFTA caused the effect of trade diversion on two non-oil commodities of Indonesia, while the three commodities showed insignificant results. The import of non-oil commodities was transferred from efficient to inefficient producers in ACFTA member countries.